Refugees and 'Native Flight' from Public to Private Schools - Semih Tumen (Institute of Labor Economics (IZA), 2019)
Native children switch from public to private primary schools in response to increased refugee concentration in the Turkish public education system. 10 percentage-point increase in refugee-to-population ratio generates, on average, 0.16 percentage-point increase in private primary school enrollment. This roughly corresponds to 1 native child switching to private education for every 31.6 refugee children enrolled in public schools — weaker than the typical estimates in the literature.
Keywords: I21; I24; H52; 330; public vs private primary education; school choice; immigration; refugees